Balintawak city haven a transient hub - Balderas, Lara Flynn Joy A. (College of Architecture, University of the Philippines Diliman, 2017)
With the current urbanization in the Philippines, Metro Manila is expanding to its neighboring provinces creating a larger metropolitan region called Greater Manila. As a result of the urban expansion, there is a large increase of people going in and out of Metro Manila putting pressure for new and further development on its borders. Balintawak in Quezon City is one of the familiar gateways to Metro Manila from Northern Luzon and vice versa. Formerly identified as an industrial center of Quezon City, Balintawak now categorized into an Agricultural Production Zone. Its strategic location linking rural and urban regions has led to the area's current gowth towards production and manufacturing of agricultural products from the north. Private market selling retail agricultural goods, vegetables and fruits from the north has spread throughout Cloverleaf, Balintawak. As envisioned by the local government of Quezon City for Cloverleaf, Balintawak to become a future commercial growth center, the proposed project would enhance the land of current market and convert it into a new development that will use and maximize the movement of people within the area. Balintawak : city haven is a 24 hour portal that offers lodging and wellness services for commuters, motorists, travelers, office workers, market goers, students, etc. It supports the day and night activity in Balintawak and serves as a sanctuary for people to rest and rejuvenate their energy from a stress and tiring day. Spaces are assigned for relaxation and leisure of the customers as well as promoting the cultural and historical image attached to the district.